Our experience in the diagnosis and treatment of postural orthostatic tachycardia syndrome, vasovagal syncope, and inappropriate sinus tachycardia in children - Sezen Ugan Atik; Reyhan Dedeoglu; Aida Koka; Funda Oztunc (KARE Publishing, 2017)
Objectives: The aim of this study was to share our experience in the diagnosis and treatment of patients who presented at our clinic with syncope, pre-syncope, dizziness, and palpitations. Study design: Patients who were treated at pediatric cardiology clinic for complaints of syncope, dizziness, and palpitations between 2014 and 2016 were enrolled in the study. Detailed history of the patients, physical examination findings, laboratory and electrocardiogram results were recorded. Tilt table test, 24-hour Holter rhythm monitoring, and exercise test were performed, as required. Patients were diagnosed as vasovagal syncope, postural orthostatic tachycardia syndrome (POTS), or inappropriate sinus tachycardia based on these findings. Treatment of the patients was evaluated. Results: Thirty patients were diagnosed as vasovagal syncope, 7 patients as POTS, and 2 as inappropriate sinus tachycardia. POTS accompanied Raynaud's phenomenon in 1 patient, hypertrophic cardiomyopathy in 1 patient, and homocystinuria in another patient. Complaints of patients with vasovagal syncope improved with non-medical therapy. Medical treatment was administered to the patients with diagnosis of POTS and inappropriate sinus tachycardia.  Conclusion: In patients with complaints of syncope, pre-syncope, dizziness, and palpitations without structural heart disease or non-rhythm problems, cardiovascular autonomic disorders, such as POTS and inappropriate sinus tachycardia should be kept in mind, as well as vasovagal syncope.